Karakteristik Nata De Seaweed (Eucheuma cottonii) dengan Perbedaan Konsentrasi Rumput Laut Gula Aren - Ikbal Syukroni; Kiki Yulianti; Ace Baehaki (Jurnal FishtecH, 2013)
The objective of this research was to determine the effect of concentration of seaweed and palm sugar to the quality of nata de seaweed. This research used factorial randomized block design with two treatments and 3 replications. The treatmens were different concentration of seaweed at 1%, 2%, and 3% and different amount of palm sugar at 7.5%, 10%, and 12.5%. The parameters observed were yield, thickness, elasticity, water content and insoluble dietary fiber of the nata. The treatment of seaweed and palm sugar with increased concentrate tended to decrease the water content of nata de seaweed, while the insoluble dietary fiber content of nata de seaweed tended to increase with treatment of seaweed and palm sugar with increased concentrate. The best treatment in this research was the treatment of 10% palm sugar and 3% seaweed (G2R3) resulting nata with insoluble dietary fiber of 1.89%.